Gene expression dynamics of natural assemblages of heterotrophic flagellates during bacterivory - Obiol, Aleix; López-Escardó, David; Salomaki, Eric D; Wiśniewska, Monika M; Forn, Irene; Sà, Elisabet; Vaqué, Dolors; Kolísko, Martin; Massana, Ramon (Microbiome, 2023)
BACKGROUND: Marine heterotrophic flagellates (HF) are dominant bacterivores in the ocean, where they represent the trophic link between bacteria and higher trophic levels and participate in the recycling of inorganic nutrients for regenerated primary production. Studying their activity and function in the ecosystem is challenging since most of the HFs in the ocean are still uncultured. In the present work, we investigated gene expression of natural HF communities during bacterivory in four unamended seawater incubations. RESULTS: The most abundant species growing in our incubations belonged to the taxonomic groups MAST-4, MAST-7, Chrysophyceae, and Telonemia. Gene expression dynamics were similar between incubations and could be divided into three states based on microbial counts, each state displaying distinct expression patterns. The analysis of samples where HF growth was highest revealed some highly expressed genes that could be related to bacterivory. Using available genomic and transcriptomic references, we identified 25 species growing in our incubations and used those to compare the expression levels of these specific genes. Video Abstract CONCLUSIONS: Our results indicate that several peptidases, together with some glycoside hydrolases and glycosyltransferases, are more expressed in phagotrophic than in phototrophic species, and thus could be used to infer the process of bacterivory in natural assemblages.
Keywords: Bacterivory; Functional genes; Glycosidases; Phagocytosis; exprese genu; Metatranscriptomics; mořská voda; Seawater; Gene Expression; Heterotrophic flagellates; Eukaryota; Peptidases; Unamended incubations; ekosystém; Ecosystem